Insights Into the Involvement of Circular RNAs in Autoimmune Diseases - Zhai, Xingyu; Zhang, Yunfei; Xin, Shuyu; Cao, Pengfei; Lu, Jianhong (Frontiers in Immunology, 2021)
Circular RNAs (circRNAs) are single-stranded endogenous non-coding RNA molecules formed by backsplicing of mRNA precursors, without covalently closed circular structures of 5'-end caps and 3'-end polyadenylation tails. CircRNAs are characterized by abundant species, stable structure, conserved sequence, cell or tissue-specific expression, and widespread and stable presence in many organisms. Therefore, circRNAs can be used as biomarkers for the prediction, diagnosis and treatment of a variety of diseases. Autoimmune diseases (AIDs) are caused by the defection of immune tolerance or abnormal immune regulation, which leads to the damage of self-organization. Due to the complexity of the pathophysiological process of AIDs, the clinical therapeutics have been suboptimal. The emergence of circRNAs brings light to the treatment of AIDs. In particular, circRNAs participate in the occurrence and development of autoimmune diseases through sponge adsorption, peptide coding, gene expression regulation and epigenetic modification. This review systematically expounds the formation, function, mechanism, characteristics of circRNAs in AIDs. With our further understanding about the pathophysiological functions of circRNAs in the pathogenesis of AIDs, circRNAs probably become reasonable, accurate, and effective biomarkers for the diagnosis and treatment of autoimmune diseases in the future.